Immunometabolism Methods and Protocols - Mishra, Suresh; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Humana, 2020)
This detailed book showcases the tremendous effort and progress made in developing techniques and protocols for the study of immunometabolism, and in utilizing recent technological advances for probing and manipulating adipose and immune cells, and subsequently, their functions and immunometabolic consequences. Written by experts in the field, many chapters use macrophages as a model immune cell type, due to their prominence in the innate immune system and the exhaustive study of their traits. Protocols using adipocytes, dendritic cells, and T cells as model cell lines, as well as measurement of glucose metabolism at the systemic level, have also been included. Written for the highly successful Methods in Molecular Biology book series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Immunometabolism: Methods and Protocols serves as a vital guide for researchers working at the important interface of immunology and metabolism.
Single-Cell Transcriptomics of Immune Cells: Cell Isolation and cDNA Library Generation for scRNA-Seq -- Monitoring Lactate Dynamics in Individual Macrophages with a Genetically-Encoded Probe -- The Conjugation of Antibodies for the Simultaneous Detection of Surface Proteins and Transcriptome Analysis at a Single-Cell Level -- Cellular Fatty Acid Analysis in Macrophage Using Stable Isotope Labeling -- Proteomic Network Analysis of Polarized Macrophages -- The Purification and Characterization of Exosomes from Macrophages -- The Isolation and Characterization of T Lymphocyte Exosomes Using Mass Spectrometry -- Analysis of Immune-Tumor Cell Interactions Using a 3D Co-Culture Model -- Studying Adipocyte and Immune Cell Crosstalk Using a Co-Culture System -- A Gene Expression Analysis of M1 and M2 Polarized Macrophages -- Simultaneous, Quantitative Characterization of Protein ADP-Ribosylation and Protein Phosphorylation in Macrophages -- The Analysis of Mycobacterium tuberculosis-Induced Bioenergetic Changes in Infected Macrophages Using an Extracellular Flux Analyzer -- Analyzing the Metabolic Phenotype of Bone Marrow-Derived Dendritic Cells by Assessing Their Oxygen Consumption and Extracellular Acidification -- The Evaluation of Mitochondrial Membrane Potential Using Fluorescent Dyes or a Membrane-Permeable Cation (TPP+) Electrode in Isolated Mitochondria and Intact Cells -- The Multiparametric Analysis of Mitochondrial Dynamics in T Cells from Cryopreserved Peripheral Blood Mononuclear Cells (PBMCs) -- The Measurement of Whole Body Glucose Homeostasis in Mice -- Immunometabolism and Its Potential to Improve the Current Limitations of Immunotherapy -- Sex Differences in Immunometabolism: An Unexplored Area -- Isolation and Preparation of Bone Marrow-Derived Immune Cells for Metabolic Analysis.
Keywords: Immunology; Chemistry; Physiology; Immunology; Chemistry/Food Science, general; Physiology